Bullous pemphigoid of Lever against the background of combined somatic pathology - E. N. Efanova; Yu. E. Rusak; E. A. Vasileva; A. A. Elmanbetova (Лечащий Врач, 2021)
Clinical observation of a rare bullous autoimmune dermatosis — bullous pemphigoid — in a patient with concomitant polyorganic somatic pathology is given. The main literature information about etiopathogenesis, clinical picture, diagnostics, differential diagnostics and treatment of Lever bullous pemphigoid are given.